Strategi Public Relations Perspektif Etika Bisnis Islam dalam Meningkatkan Usaha Penjualan pada Rumah Makan Bakso Bob Kuala Lumpur Malaysia - Pradita Putri Angelica; Fatkhur Rohman Albanjari; Adib Khusnul Rois (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the application of Public Relations strategies in increasing sales at Rumah Makan Bakso Bob, Kuala Lumpur, from the perspective of Islamic business ethics. The Public Relations strategies implemented include publicity, persuasion, argumentation, and image, which are integrated with Sharia values such as honesty, transparency, and social responsibility. The research adopts a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The study reveals that publicity strategies using social media effectively enhance brand awareness, while persuasion emphasizing halal product quality and friendly service successfully builds customer loyalty. Argumentation strategies, such as transparency in production processes and halal certification, strengthen consumer trust. Meanwhile, image-building efforts through social contributions, such as food-sharing programs, create a positive reputation that supports business growth. These strategies align with the principles of Islamic business ethics, including unity, equilibrium, free will, responsibility, and benevolence. As a result, Rumah Makan Bakso Bob has not only significantly increased its sales but also generated positive social impacts within the community. This study offers insights into how Islamic values can be integrated into Public Relations strategies to achieve sustainable business success.